Defining an effective EFL teacher: Insights from Filipino English educators - Marsevani, Maya; Nurlaily, Nurlaily (EduLite: Journal of English Education, Literature and Culture, 2025)
The demand for native and native-like English teachers in Asia has shifted preferences toward educators from countries like the Philippines, known for its high level of English fluency and nativized language forms. This study examines the unique challenges and attributes of Filipino English as a Foreign Language (EFL) teachers in Indonesia, focusing on their relatability to students and the high expectations placed on them as expatriates. The study utilized a qualitative case study approach, gathering insights from six Filipino EFL teachers working in Batam, Indonesia, across five schools. Data were collected through semi-structured interviews with 11 questions, complemented by classroom observations and document analysis. The teachers, with varying levels of experience, shared their classroom challenges and strategies for effective teaching. Findings highlight the importance of adaptability, cultural awareness, and pedagogical flexibility in effective EFL teaching. Teachers emphasized the need for instructional strategies tailored to students' diverse learning needs, integrating structured curricula with supplementary materials. Their reflections also underscored the value of self-awareness and continuous professional development in improving teaching efficacy. This study provides insights into the complexities of being an expatriate EFL teacher in Indonesia. The findings suggest that EFL teacher training should prioritize cultural sensitivity, adaptability, and flexible pedagogical approaches. Future research could expand on these findings, exploring the experiences of Filipino teachers in different regions of Indonesia, to further understand the dynamics of expatriate teaching in Asia.